PENGARUH PERILAKU PEMILIK ATAS ISU MANAJEMEN LINGKUNGAN TERHADAP KINERJA KEUANGAN MELALUI CUSTOMER SATISFACTION PADA PERUSAHAAN DI WILAYAH SURABAYA - Seputro, Swandayani (Business Accounting Review, 2016)
The aim of this study was to know the influence of the owners behavior on the issue of environmental management toward financial performance, with customerâs satisfaction as an intervening variable. The type of research was quantitative research. The sample was the owner of the companies in Surabaya, totaling 56 peoples. This study used analysis techniques Partial Least Square (PLS). The results showed the owners behavior on environmental management issues affect on each of the customerâs satisfaction and financial performance, the better the ownerâs behavior of environmental management issue, the more satisfied customers and better financial performance. In addition, it was concluded that customerâs satisfaction also affect financial performance, so the higher customerâs satisfaction, the higher the companys financial performance.